The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/tax.12071
|View full text |Cite
|
Sign up to set email alerts
|

Reinstatement and revision of the genus Adelmeria (Zingiberaceae) endemic to the Philippines

Abstract: In 1909, Ridley published Adelmeria characterized by its congested terminal inflorescence with large persistent floral bracts. All five species at some point placed in Adelmeria were synonymized in Alpinia by Loesener and subsequent authors. Several phylogenetic studies revealed that Alpinia is highly polyphyletic, suggesting that it should be split into several genera. In the present study, we sampled all five species initially placed in Adelmeria plus additional ones with a similar morphology. The combined a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…the characters used by Smith were scattered within the three major subclades of Plagiostachys ). The latter paper, as well as recent molecular studies in tribe Alpinieae (Kress et al , De Boer et al , Docot et al ), also demonstrated that Plagiostachys is within the Alpinia zerumbet clade where the bulk of Alpinia Roxb. species are nested.…”
Section: Introductionmentioning
confidence: 75%
“…the characters used by Smith were scattered within the three major subclades of Plagiostachys ). The latter paper, as well as recent molecular studies in tribe Alpinieae (Kress et al , De Boer et al , Docot et al ), also demonstrated that Plagiostachys is within the Alpinia zerumbet clade where the bulk of Alpinia Roxb. species are nested.…”
Section: Introductionmentioning
confidence: 75%
“…The DNeasy Plant Mini Kit was used to extract total genomic DNA following the manufacturer's protocol. The ITS and trn K/ mat K regions of the new species were amplified using Docot et al (2019b) PCR mix and thermal profile. PCR products were sent to Macrogen (Seoul, Korea) for purification and sequencing.…”
Section: Methodsmentioning
confidence: 99%
“…In 2018, De Boer et al recircumscribed the genus Amomum Roxb., which for the Philippine flora resulted in the addition of Meistera Giseke and Wurfbainia Giseke and bringing the number of genera to 16. In a first step towards recircumscribing the genus Alpinia , Docot et al (2019) reinstated the genus Adelmeria Ridl. endemic to the Philippines, thus reaching 17 as the current number of ginger genera in the country.…”
Section: Introductionmentioning
confidence: 99%